COMPARATIVE ANALYSIS OF COGNITIVE LEARNING OUTCOMES IN SOCIAL STUDIES FOR PHASE D OF KURIKULUM MERDEKA (INDONESIA’S MERDEKA CURRICULUM) - Nico Tri Raharjo Sapoetro; Bagja Riyanto; Saliman (SOSIOEDUKASI, 2026)
The Merdeka Curriculum includes Learning Outcomes (Capaian Pembelajaran or CP) as a key component, serving as the primary reference for teachers in planning and conducting instruction. Recently, the Head of the Agency for Standards, Curriculum, and Educational Assessment (BSKAP) revised the CP, replacing version 032/H/KR/2024 with 046/H/KR/2025. This revision introduces changes that directly affect the expected cognitive levels of student achievement. This research seeks to compare the substance of the Learning Outcomes documents for Social Studies (Ilmu Pengetahuan Sosial) in Phase D, to assess the degree of cognitive level changes, and to examine their implications for instructional direction, competency focus, and the intended depth of students’ cognitive abilities. The study uses a comparative document analysis approach.The findings reveal a transition from the dominance of C2 (Understanding) to a broader distribution across higher levels in the revised Bloom’s Taxonomy, including C3 (Applying), C4 (Analyzing), C5 (Evaluating), and C6 (Creating). New operational verbs such as explain, predict, identify, analyze, evaluate, and elaborate emphasize a focus on Higher Order Thinking Skills (HOTS). In Phase D Social Studies learning, teachers need to design strategies based on case studies, analytical discussions, collaborative projects, and creative assignments to encourage analysis, evaluation, and creation, making learning more critical, reflective, and innovative.